PENGEMBANGAN KITCHEN MANAGEMENT SYSTEM PADA POINT OF SALE UNTUK USAHA KULINER - NAUFAL RAFI HIDAYAT; Sri Kusumadewi (PENDIDIKAN SAINS DAN TEKNOLOGI, 2026)
The order management process in a restaurant kitchen is a crucial aspect that directly influences service quality and customer satisfaction. However, many restaurants still rely on manual communication between cashiers and kitchen staff to deliver order information. This approach often leads to communication delays, misunderstandings, and an increased risk of human error that can negatively affect kitchen operations. This study discusses the implementation of a web-based Kitchen Dashboard designed to assist kitchen staff in monitoring and managing orders more effectively and efficiently. The system is capable of displaying queued orders, active orders, and completed orders in real time through an API polling mechanism. The application was developed using JavaScript and an object-oriented programming approach consisting of three main classes: KitchenApiService, KitchenUIRenderer, and KitchenDashboard. In addition to presenting order information in a structured manner, the system automatically updates data every three seconds without requiring manual page refreshes. The implementation results indicate that the Kitchen Dashboard improves the speed of information delivery, reduces communication errors, and supports smoother restaurant kitchen operations.